2020
DOI: 10.3390/atmos11101041
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Weather and Seasonal Forecast Information Concerning the Peri-Urban Farmers’ Needs in the Lower Ganges Delta in Bangladesh

Abstract: Skillful weather and seasonal predictions have considerable socio-economic potential and could provide meaningful information to farmers and decision-makers towards agricultural planning and decision-making. Peri-urban farmers in the Lower Ganges Delta need skillful forecast information to deal with increased hydroclimatic variability. In the current study, verification of European Centre for Medium-Range Weather Forecasts’ System 5 (ECMWF SEAS5) seasonal prediction system is performed against ground observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The potential of Scientific Forecast Knowledge (SFK) in improving the adaptation capabilities of small-scale farmers had been highlighted in several studies (Dunning et al, 2016;Gbangou et al, 2019;Naab et al, 2019;Nyadzi et al, 2018;Paparrizos et al, 2020). Ghana Meteorological Agency in the year (GMet, 2016 in collaboration with ESOKO and CGIAR provided information on the seasonal onset of rains and daily weather forecast via conventional SMS to farmers in several communities (ESOKO, 2016;Nyadzi et al, 2018).…”
Section: Scientific Forecast Knowledge Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential of Scientific Forecast Knowledge (SFK) in improving the adaptation capabilities of small-scale farmers had been highlighted in several studies (Dunning et al, 2016;Gbangou et al, 2019;Naab et al, 2019;Nyadzi et al, 2018;Paparrizos et al, 2020). Ghana Meteorological Agency in the year (GMet, 2016 in collaboration with ESOKO and CGIAR provided information on the seasonal onset of rains and daily weather forecast via conventional SMS to farmers in several communities (ESOKO, 2016;Nyadzi et al, 2018).…”
Section: Scientific Forecast Knowledge Predictionsmentioning
confidence: 99%
“…Considerable progress has been made in weather and climate forecasting (Doblas-Reyes et al, 2013), but because of its probable nature, seasonal forecasting presents systematic errors which is a significant challenge globally (Bauer et al, 2015). Much of the information generated for weather and climate predictions is limited where practical decision-making is concerned, leading to less accurate forecasts, as predictions are being made more into the future (Paparrizos et al, 2020).…”
Section: Challenges Of Scientific Forecast Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, accessibility of hydro-climatic information services is of utmost importance for sustainable rainfed agricultural practices and leads to higher yields and minimum risk of crop failure [10,11] Some studies have shown that Climate Information Services (CIS) can help farmers to reduce their vulnerability to drought and other climate extremes and allow them to maximize agricultural productivity [12][13][14]. The underlying assumption in the current practices of CIS is that if location-specific, timely, and skillful information is provided to farmers, they would be able to improve their farming practices [15][16][17]. This one-directional model of providing CIS, however, has shown to be flawed as farmers tend not to trust scientific information, which is dynamical weather forecasts, and experience difficulties in interpreting and applying the scientific forecasts into daily farming actions.…”
Section: Introductionmentioning
confidence: 99%
“…Defining a strategy to sustain the coproduction process was found to be a critical design principle (Table 5. 6). In this regard, it is important to reflect on WCIS sustainability and inclusiveness.…”
mentioning
confidence: 99%